HBR guide to unlocking creativity - Blaker, Lyle; Hendrix, Kitty (Harvard business review guides., 2023)
Without creativity, innovation is impossible. Creativity is the key driver of innovation, but too many teams and projects are organized in ways that stifle new ideas. It's your job as a manager to create the right conditions for creativity to thrive-and to be part of the process yourself. Fortunately, anyone can use a method-driven approach to teach and learn to be more creative. The HBR Guide to Unlocking Creativity will show you how to design a work environment that allows you and your team to change how you think, reach your creative potential, and achieve groundbreaking results. This guide will help you: get out of a creativity rut; overcome the fear that blocks creativity; balance creativity with productivity; model a creative mindset for your team; encourage curiosity and experimentation; avoid breakdowns in creative collaboration; and bring breakthrough ideas to life. Arm yourself with the advice you need to succeed on the job, with the most trusted brand in business. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.